ANALISIS KERJA SAMA MILITER ANTARA TURKI-AZERBAIJAN TAHUN 2020 TERKAIT ANCAMAN ARMENIA DALAM KONFLIK NAGORNO-KARABAKH MELALUI PERSPEKTIF BALANCE OF THREAT - Nur Vita Dewan Tari; Annisa Andien Armadhani; Egi Purnama Putra; Hilmi A Ibrahim; Renitha Dwi Hapsari (Halu Oleo University, 2025)
The purpose of this research discuss the reasons for Azerbaijan to strengthen military cooperation with Turkey in the Nagorno-Karabakh conflict using the Balance of Threat perspective developed by Stephen M. Walt. This research uses a descriptive qualitative method with data collection techniques through literature studies from scientific journals, official government reports, and analysis of strategic studies institutions. This military cooperation was formed in response to the perceived threat from Armenia, which is considered to have aggregate power, geographical proximity to Azerbaijan's strategic territory, offensive power, and aggressive intentions. The results show that this cooperation is not only based on Turkey's strategic interests in expanding its influence in the Caucasus region. In the Balance of Threat framework, this alliance is a form of balancing against external threats, especially from Armenia and its supporting regional actors.